Adsorption of phosphates on a novel eggshell Ca-modified anaerobic sludge-based biochar: Adsorption performance and mechanism - Guang-Hui Zhuo; Dong-Xin Xue; Long-Fei Huang; Qi Wang; Guangcan Zhu; Chu-Ya Wang (PLoS ONE, 2025)
Efficient recovery of phosphate from wastewater is required due to phosphorus (P) pollution and resource scarcity. In this study, a Ca-modified biochar (ESBC-1) was developed to enhance phosphate adsorption by co-pyrolysis of digestate from anaerobic fermentation and waste eggshell (1:1 mass ratio) at 700 °C. Under ideal conditions (1 g/L, pH 3–10), ESBC-1’s adsorption capacity fluctuates by less than 8% within this pH range, exhibiting excellent pH adaptability, and the phosphate adsorption capacity of ESBC-1 was 97.74 mg/g, which was 7.9 times higher than that of unmodified biochar (SBC). The effect of common cations (Na ⁺ , K ⁺ , Mg 2 ⁺ , Ca 2 ⁺) and anions (Cl ⁻ , SO₄ 2 ⁻) on the adsorption was small, but due to competitive binding and pH, CO₃ 2 ⁻ and HCO₃ ⁻ inhibited the adsorption substantially. The process followed the pseudo-second-order kinetic model (R 2 = 0.9988), which indicates that chemical adsorption is the rate-limiting step, and Freundlich isotherm model (R 2 = 0.9763), which reflects heterogeneous adsorption sites on the ESBC-1 surface. At 298 K, the maximum Langmuir adsorption capacity is 529.10 mg/g, while that of SBC is only 287.72 mg/g — this confirms the significant promotion effect of Ca modification. According to characterization (SEM-EDS, FTIR, XRD, XPS), adsorption mostly happened by chemical precipitation, where surface Ca 2 ⁺ was hydrolyzed from Ca(OH)₂ and combined with phosphate to form insoluble hydroxyapatite (Ca₅(PO₄)₃OH). In the actual biogas (TP = 24.49 mg/L, pH = 8.64), ESBC-1 was used at a dosage of 8 g/L, and phosphate removal rate reached 75.23%. This work demonstrated a sustainable “waste resource utilization-pollution control” strategy by converting sludge and eggshell into an effective phosphate adsorbent, suggesting a new way to address the problems of waste valorization and eutrophication.